Best 170 law schools - Owens, Eric; Princeton Review (Firm) (New York : Random House, 2007)
Offers information about admission, academics, and social life at top U.S. and Canadian law schools
Includes index
Keywords: Law schools -- United States -- Directories; Law schools -- Canada -- Directories